Kajian Peningkatan Manfaat Pada Bendungan Tugu Kabupaten Trenggalek - Wahyuningdyah, Mey; Juwono, Pitojo Tri; Rispiningtati, Rispiningtati (Fakultas Teknik, Universitas Brawijaya, 2012)
At the beginning Tugu dam was planned to supply water demand and irrigation water. In this study will be reviewed on a large electric power can be generated from the utilization of the reservoir outflow discharge and increase the value of benefits when Tugu dam is used as power plant and tourism places.Power generation at Tugu dam is planned in base load. Francis turbine is selected with optimum installed power is 400 kW, which capability of producing energy is 2,140,382.328 kWh / year. Tugu dam tourism region plans to use the land area of 9.86 hectares with cottage, water and tourist playground, swimming pool, restaurant and shop / shopping tour. Based on economic analysis conducted, can increase in the value of BCR, NPV and IRR. BCR value of 1.115 which was originally changed to 1.142; the original NPV of Rp. 36,705,066,329.00 turned into Rp.53.154.809.819,00; the original IRR 13.057% turn into 13.408%.Key words: power generation, tourism, economic analysis.